Context, mechanisms and community engagement in implementation strategies: a systematic review protocol of implementation strategies designed using implementation mapping - Eunyoung Kang; Maria E Fernández; Serena Rodriguez; Gill ten Hoor; Derek W Craig; Jennifer Stockton (BMJ Open)
Introduction Implementation Mapping (IM) has increasingly been used for the design and/or selection and tailoring implementation strategies to promote the effective translation of evidence-based interventions into practice. IM is a tool for guiding the systematic, iterative, step-by-step design process that helps guide the co-creation of theory-based, evidence-informed implementation strategies. This protocol aims to describe the methods of the planned systematic review that will (1) examine the overall landscape of IM in developing implementation strategies, (2) explore the mechanisms of implementation strategies developed using IM and (3) investigate the use of IM and community engagement in the development of implementation strategies. This review will produce synthesised evidence that will describe how IM has been used in selecting, designing and tailoring implementation strategies, with a focus on implementation mechanism and community engagement.Methods and analysis We will include peer-reviewed original English articles that describe the use of Implementation Mapping or Intervention Mapping to design implementation strategies. We will search Medline Ovid, PsycInfo, Embase, CINAHL and Web of Science using the following terms: ‘Implementation Mapping’ and ‘Intervention Mapping’. At least two reviewers will independently screen the records to examine the eligibility. After several rounds of consistency testing of data extraction among at least two reviewers and confirming the consistent coding among the reviewer team, one coder will proceed with the data extraction. In case of uncertainty, we will reach a consensus through interactive reviewers’ meetings and in consultation with a senior author. We examined the risk of bias in individual studies using the quality assessment tool developed by Hawker et al in 2002. We will synthesise and present the data by each research aim.Ethics and dissemination Ethics approval was not required. Findings will be shared via peer-reviewed journals, and data from the included studies will be made openly accessible.